براہوئی انشائیہ نا تحقیقی او تنقیدی تبصرہ غاتا اسہ جاچ اس: Research and Critical Analyses of Brahui Inshaaiyaa - Bangulzai, Abdul Latif (Al-Burz, 2009)
Prose-writing is a style of the literature which has been carried out in each and every neighboring languages of the Brahui speaking people. Being a style of literature, prose-writing differentiates itself from fiction writing in different stages.The history of prose-writing is not so long in the Brahui literature, but it is has enriched one of the major portions of the Brahui language. Prose-writing started in the early days of 1970, when Kamil al Qadris’” Sirox” was published. This was the basic book which opened the doors for the forthcoming prose-writers of the Brahui literature. The Brahui prose-writing a clear picture of the Brahui society and psyche. In this paper, all aspects of the prose concerning to the Brahui literature will be discussed in detail and it will be shown that how the prose writing has been effective in the Brahui literature.